Deviation from Tribal Traditions: The Other Face of Poetry in Pre-Islamic Arabia - Andri Ilham (Universitas Negeri Jakarta, 2022)
Poetry in pre-Islamic Arabia is a social document (dīwān) and the most authoritative source possessed by the Arab people. This fact does not imply that pre-Islamic poetry is monotonous with a single pattern of tendency. On the contrary, pre-Islamic poetry is a collection of various tendencies that are divided into different aspects and diversities, both in expression (al-ta‘bīr) and content (al-muḥtawá). Therefore, this study aims to describe the facts about pre-Islamic poetry that not only revolves around tribal fanaticism (‘aṣabīyah qabalīyah) but also exhibit deviations from tribal (qabīlah) traditions. The research method employed in this study essentially utilizes historical methods, including the heuristic, criticism, and interpretation steps in analyzing the acquired data sources. The results of this study indicate that the other side of the content of pre-Islamic poetry which deviates is reflected in two tendencies: first, deviations that arise from individual subjective experiences (al-tajribah al-dhātīyah), such as the poems of Imru’ al-Qays and Ṭarafah ibn al-‘Abd; second, deviations that arise from political and ideological experiences (al-tajribah al-siyāsīyah al-īdiyūlūjīyah), as reflected in the poems of the brigand (Ṣa‘ālīk) group.